Efektivitas Eco Enzyme Terhadap Kadar Chemical Oxygen Demand (COD) Limbah Cair Industri Farmasi - Mohammad Rheza Albin Wahyudi; Rita Dwi Ratnani; Indah Hartati (Fakultas Teknik Universitas Wahid Hasyim, 2026)
Pharmaceutical wastewater management remains a major environmental challenge due to its high content of complex organic pollutants. This study evaluated the effectiveness of eco enzyme as an environmentally friendly alternative for reducing Chemical Oxygen Demand (COD) in pharmaceutical industrial wastewater. Eco enzyme was produced by fermenting organic waste (apple peels, yam, and wax apple) with water and palm sugar at a ratio of 10:3:1 for six months. The experiment investigated eco enzyme concentrations of 2%, 4%, 6%, 8%, and 10% under contact times of 48, 96, and 144 hours. The results demonstrated that eco enzyme effectively reduced COD under specific operational conditions. The optimal performance was achieved at a 6% concentration with a 96-hour contact time, reducing COD to 25.84 mg/L. Higher concentrations and prolonged contact times did not improve treatment efficiency, indicating enzyme saturation and limited catalytic effectiveness. These findings highlight the potential of eco enzyme as a sustainable, natural coagulant for pharmaceutical wastewater treatment and provide a basis for optimizing operational parameters in future studies.